THE EFFECTIVITY OF NUTMEG PROCESSING AND PACKAGING REFORMULATION ACTIVITY IN INCREASING THE PUBLIC WELFARE IN JAYA VILLAGE OF TIDORE ISLANDS - Suwandi S. Sangadji; Mustasyfa Thabib Kariadi; Saiful Rachman (Universitas Panji Sakti, 2020)
Low farmer welfare level is one development problem in Tidore. This is explained in the medium-term regional development plan of Tidore Islands 2016-2021. Regarding to the public welfare phenomena, this research aims at knowing the influence magnitude on the effectiveness of nutmeg processing and packaging reformulation activity to the public welfare in Jaya village. The method used in this research was quantitative research conducted by survey sample research approach. The sampling used from the population used stratified random sampling technique. The data collection used literature review, research questionnaire and observation. Data analysis used included item validity test, instrument reliability test, correlation coefficient measurement, determination coefficient measurement, hypothesis test using t-test and regression equation measurement. The research result showed that there was a positive and significant effectivity of nutmeg processing and packaging reformulation activity to the public welfare in Jaya Village of Tidore Islands.